2022
DOI: 10.1007/s00167-022-06871-1
|View full text |Cite
|
Sign up to set email alerts
|

Posteriorly positioned femoral grafts decrease long-term failure in anterior cruciate ligament reconstruction, femoral and tibial graft positions did not affect long-term reported outcome

Abstract: Purpose To investigate the effect that femoral and tibial tunnel positions have on long-term reported and clinical outcome and to identify a safe zone based on favourable outcome. Methods Seventy-eight patients from a previous randomised controlled trial were included and were followed with a mean follow-up of 11.4 years. All patients had primary trans-tibial anterior cruciate ligament reconstruction performed. The femoral and tibial tunnel positions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…This greater rotational instability increases shear stress on ACL-R, cartilage, and menisci, which increases the risk of ACL re-rupture and wear (27,28,29). The higher re-rupture rate of more anteriorly placed femoral tunnel apertures was also shown in a recent subanalysis of a randomized controlled trial with a follow-up of about 11 years (30). This study identified a safe zone parallel to the Blumensaat line at the most posterior 35% of the femoral condyle.…”
Section: Reasons Of Failuresupporting
confidence: 67%
“…This greater rotational instability increases shear stress on ACL-R, cartilage, and menisci, which increases the risk of ACL re-rupture and wear (27,28,29). The higher re-rupture rate of more anteriorly placed femoral tunnel apertures was also shown in a recent subanalysis of a randomized controlled trial with a follow-up of about 11 years (30). This study identified a safe zone parallel to the Blumensaat line at the most posterior 35% of the femoral condyle.…”
Section: Reasons Of Failuresupporting
confidence: 67%
“…Stiffness was defined as loss of range of motion (ROM) > 10° of flexion or > 3° of extension [19]. Clinical failure encompassed all retears as well as patients with Lachman ≥ 2B, pivot shift ≥ 2 + , or KT difference ≥ 5 mm at final follow‐up [8, 13].…”
Section: Methodsmentioning
confidence: 99%
“…The surgeon must be certain that they see the true posterior margin of the condyle and not J o u r n a l P r e -p r o o f mistake the lateral intercondylar ridge for the posterior margin. The most common error is overly anterior placement of the femoral tunnel, so care is taken to place it posteriorly on the condyle [57]. On the tibial side, the tibial spine, intermeniscal ligament, and anterior horn of the lateral meniscus are landmarks for tibial tunnel placement [24,31,58].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%